Effect of organic matter in a recovered bauxite soil in Jamaica - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2019)
The powerful role of Organic Matter in recovering degraded lands is documented in Jamaica, bringing life back to farming areas where mining was once practiced.